Cadmium adsorption by E. coli with surface displayed CadR1. Issue 21 (6th March 2015) - Liu, Q.; Yuan, F.; Liang, Y.; Li, Z.
<x xml:space="preserve">Abstract</x> CadR is a metal-binding protein first isolated from rhizobacterium Pseudomonas putida.